If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 10c + 9v + 6c + -7v = 0 Reorder the terms: 10c + 6c + 9v + -7v = 0 Combine like terms: 10c + 6c = 16c 16c + 9v + -7v = 0 Combine like terms: 9v + -7v = 2v 16c + 2v = 0 Solving 16c + 2v = 0 Solving for variable 'c'. Move all terms containing c to the left, all other terms to the right. Add '-2v' to each side of the equation. 16c + 2v + -2v = 0 + -2v Combine like terms: 2v + -2v = 0 16c + 0 = 0 + -2v 16c = 0 + -2v Remove the zero: 16c = -2v Divide each side by '16'. c = -0.125v Simplifying c = -0.125v
| 32=18-2k | | -191=-7-8(-5+4a) | | 5+24x=23x | | 5+24x=23 | | 3.1r=13.95 | | 7a+10b+6a-3b= | | -5+24x=23 | | 4=n+10 | | x+3=68 | | 7j+4j= | | 5x^4=5x | | 4f-8=-4n-12 | | 8+4(-8+3)=-12 | | 6+(n+7)2=25 | | (4x-16)=(2x+6) | | -6x=114 | | -4x-12y=12 | | 9u-2u= | | 7x-7=-5+2x-12 | | 6x+4=2(2x-5) | | 7c+5c= | | 1.5x-5=4x | | 2(2x-5)-3+2=x+9 | | b^3-4b^2=21b | | -16=(-x) | | 9f+2f= | | 7v+4v= | | -38-(-14)= | | ln(8-x)=ln(3x-2)+ln(x+2) | | -6z+8=-13 | | y=.66x-1.25 | | 1.5y-12=60 |